(untitled) (Research, Society and Development, 2020)
This study focuses on Youth and Adult Education in the countryside and aims to analyze the aspects that have contributed to school permanence in the rural settlement 25 de Maio, observing the struggle for Rural Education in the context of land reform. It is a qualitative, descriptive and explanatory research, guided by the dialectical method. For the collection of materials in the field, semi-structured interviews, participant observation and document analysis were used. It was found that school stay in the field is related to the categories school management, teaching practice and pedagogical practice. The Municipal Department of Education is responsible for the organization of teaching, pedagogical support and provision of EJA within this settlement. Teachers carry out basic work consisting of home visits, but the school lacks pedagogical support. It was found that the majority of students are rural workers, aged between 32 and 50 years old, who remained in the EJA in order to complete their schooling process (elementary school II and high school) and obtain certification. Therefore, this study allows us to reflect on the challenges of EJA in settled areas paying attention to school permanence in the field and brings notes for future research.